TIPOLOGI RAGAM HIAS RUMAH TINGGAL KELUARGA BAKRI ZAED DI BALUWARTI SURAKARTA (Typology of Decoration of the Family Bakri Zaed's Residence at Baluwarti Surakarta) - Nafi'ah Solikhah (Tesa Arsitektur, 2012)
Baluwarti was originally a residential area for families and courtiers of Kasunanan palace. Together with the development of the economic activity types and the increasing economic potentials of the community of Ba/uwarti's, we then find residential houses having mixing styles of Javanese, European, Chinese, and Islamic. The problems found In the field is the presence of absorption and adaptation of elements of Javanese culture and foreign cultures that create decoratlva typology of Bakri Zaed's family residence. The objective of this study was to Identify the decorative typology that is applied at Bakri Zaed's family residence. This study is qualitatively descriptive having explorative descriptive analysis approach. The factors to be examined are the characters of the decoration (motifs, pattems, materials, and color), and the style applied. Based on study results; it could be concluded that the typology of decoration of Bakri Zaed's family residence is attachment/eclectics of several styles, which are: Java, Art Deco, Art Nouveau, Middle East, and China. There was no standardized character and style. Absorption process to perform self-existence that is influenced by social, level of economic potential, culturaV political status (related to the palace Kasunanan) and the closed circumstances Is based on the owner's tastes.